Ablation-resistant composite material as well as preparation method and application thereof
By blending polyadipanyl hexanediamine and polyphenylene ether and adding a specific proportion of reinforcement fillers and flame retardants, a resistant composite material is prepared, which solves the problem of insufficient ablation resistance performance of the battery in the battery pack of new energy vehicles, and achieves both high mechanical properties and ablation resistance.
Patent Information
- Application Number
- CN202510027064.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
AI Technical Summary
The batteries in the battery pack of new energy vehicles are prone to get out of control after friction or impact, resulting in thermal runaway, combustion or explosion. The flame temperature of traditional metal ablation-resistant materials is insufficient, and they are large in weight, long molding cycle and high cost. While improving mechanical properties, the ablation-resistant temperature still cannot meet the high standards of new energy vehicles.
By blending polyadipanyl hexanediamine (PA66) with polyphenylene ether, adding a special proportion of reinforcement filler, flame retardant, compatibilizer, flame retardant synergist and processing aid, the preparation was made by melt mixing to obtain ablation-resistant composite material with high mechanical properties, strong ablation resistance and no deformation.
It achieves high melt index, tensile strength, bending strength and simple-supported beam notched impact strength at 280℃ and 5kg load, and burns through time at 1000℃ for more than 30 minutes. The surface is smooth and has no floating fibers, and has good flame retardant performance and long service life.
Smart Images

Figure CN119684788A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an ablation-resistant composite material and a preparation method and application thereof. Background Art
[0002] With the continuous development of the country's new energy vehicle technology and the vigorous promotion of the power battery industry, the demand for new energy vehicle battery packs will also usher in explosive growth in recent years, which will bring huge development opportunities for upstream polymer modified materials. New energy vehicle battery packs are the core components of electric vehicles, mainly composed of battery cells, modules and cells. The battery in the new energy vehicle battery pack has always been the "lifeline" restricting the development of new energy vehicles. Major power battery companies and vehicle manufacturers are striving to break through technical bottlenecks. With the improvement of the endurance of new energy vehicles, higher requirements are put forward for batteries and their supporting products in terms of high safety, lightweight, high energy density and long cycle life.
[0003] The endurance of new energy batteries has been improved, but the charging speed is too fast, which also causes the battery to lose control after friction or collision, causing battery heat, battery combustion or explosion, posing a threat to people's personal safety. Therefore, delaying battery thermal runaway and leaving people enough time to escape has become a top priority. In order to avoid the harm caused by battery heat, a corrosion-resistant cover is often set outside the new energy battery to protect the battery. For example, patent CN113771950A discloses a new energy vehicle integrated die-cast chassis anti-collision and anti-flammability method, and the manufacturing of the automobile chassis is realized through the die-casting process. The steel pipe longitudinal beam is embedded in the die-cast chassis, and the resilience of the steel pipe is used to prevent the occupants from being clamped in a collision accident; the battery pack is installed in the steel pipe longitudinal beam and the U-shaped cross beam, and high temperature protection is provided for it. When the battery burns, the steel pipe is not burned through, and the tail nozzle of the steel pipe is far away from the rear of the car to ensure that the battery pack will not ignite the body when it burns. Multiple steel pipes with built-in batteries divide the large-capacity battery pack into several small-energy battery packs, which improves the safety performance of preventing combustion. However, with the development of new energy batteries, the ablation resistance of metals has failed to meet the requirements for their use. Among them, the ablation temperature of aluminum alloy is about 750°C, while the flame resistance temperature of new energy batteries even reaches 1500°C. Therefore, the ablation resistance temperature of metal materials is far from meeting the current requirements, and the high weight, long molding cycle and high cost of metal materials have become disadvantages that cannot be ignored.
[0004] In order to replace metal materials and protect new energy batteries, the heat resistance and ablation resistance of resin materials have been applied. For example, patent CN115594970A discloses an ablation-resistant polyphenylene ether composition and its preparation method, including PPE resin, maleic anhydride grafted PPE resin, polyamide resin, phosphorus-containing flame retardant and glass fiber. This technical solution can significantly improve the ablation resistance of polyphenylene ether by introducing special polyamide resin and appropriate amount of flame retardant.
[0005] CN118006109A discloses a polyphenylene ether resin composition and its preparation method and application. The polyphenylene ether resin composition of the present invention comprises the following components in parts by weight: 18-51 parts of polyphenylene ether resin and / or maleic anhydride grafted polyphenylene ether resin, 18-42 parts of crystalline polyamide, 4-11 parts of amorphous polyamide, 1-13 parts of phosphorus-containing flame retardant, and 8-42 parts of glass fiber; the melting point of the crystalline polyamide is ≥210°C. The present invention can improve the ablation resistance while maintaining good product appearance performance by adding crystalline polyamide and amorphous polyamide at the same time.
[0006] Polyphenylene ether resin has the advantages of excellent mechanical strength, stress relaxation resistance, low density, heat resistance, good flame retardancy, good dimensional stability and excellent electrical properties. Blending with nylon, glass fiber and other materials can effectively improve the mechanical properties and ablation resistance of polyphenylene ether. However, the resin material prepared in this way still cannot meet the ablation resistance requirements of new energy batteries.
[0007] Therefore, the ablation resistance of the new energy battery cover is extremely important, but the ablation resistance temperature of the traditional metal cover is low and cannot meet the ablation resistance requirements of the current new energy batteries. The resin material prepared by mixing polyphenylene ether with nylon and other materials can improve the mechanical properties of the material while also improving the ablation resistance of the resin material. However, its ablation resistance temperature still cannot meet the high standards of new energy vehicles, and the material's easy volatility and easy warping are still problems that need to be solved urgently. Summary of the invention
[0008] In view of the above problems, the present invention provides an ablation-resistant composite material, a preparation method and application thereof, wherein a composite material with high mechanical properties, strong ablation resistance and no deformation is prepared by blending polyhexamethylene adipamide (PA66) and polyphenylene ether, adding reinforcing fillers, compatibilizers, flame retardants, and specific flame retardant synergists in special proportions and processing aids, and then melt mixing.
[0009] The present invention provides an ablation-resistant composite material. The ablation-resistant composite material is prepared by melt-mixing polyhexamethylene adipamide, polyphenylene ether, a reinforcing filler, a flame retardant, a flame retardant synergist, a compatibilizer and a dispersant; the ablation-resistant composite material has a melt index of 40-55 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 110-140 MPa, a flexural strength of 150-180 MPa, and a simply supported beam notched impact strength of 4-7 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0010] Furthermore, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 25-50 parts by weight; Polyphenylene ether is 10-30 parts by weight; The reinforcing filler is 25-35 parts by weight; The flame retardant is 10-16 parts by weight; The flame retardant synergist is 0.1-6 parts by weight; The compatibilizer is 0.1-6 parts by weight; The dispersant is 1-2 parts by weight.
[0011] Furthermore, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g.
[0012] Furthermore, the intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g.
[0013] Furthermore, the reinforcing filler is organosilicon-modified glass fiber, the glass fiber in the organosilicon-modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:(3-3.75).
[0014] Furthermore, the manufacturer of the organosilicon-modified glass fiber is Taishan Glass Fiber, with the brand name TFG436.
[0015] Furthermore, the flame retardant is prepared by compounding diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of (3-4):1:0.5.
[0016] Furthermore, when the diethylaluminum hypophosphite in the ablation-resistant composite material burns, it forms a strong acid polyphosphoric acid to dehydrate the plastic into carbon, and forms a carbon film on the surface of the material to isolate the air and flame; when melamine polyphosphate burns, it can sublimate and absorb heat to isolate the air, and can also form a carbon layer to isolate the flame; ceramic powder is a silicate composite, which has a significant sintering and porcelain-forming effect during high-temperature combustion, and can effectively improve the flame retardancy of the material.
[0017] Furthermore, the flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane.
[0018] Furthermore, the compatibilizer is maleic anhydride grafted polyphenylene ether.
[0019] Furthermore, the dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of (3-5): (1-3).
[0020] The present invention also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist, and feeding the mixture through a loss-in-weight scale from a side feeding port in the seventh temperature zone of the twin-screw extruder; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0021] Furthermore, in the step 1, the mass ratio of the polyhexamethylene adipamide, the polyphenylene ether, the compatibilizer and the dispersant is (25-50): (10-30): (0.1-6): (1-2).
[0022] Furthermore, in step 1, the mixing speed is 300-500 r / min, and the mixing time is 2-4 min.
[0023] Furthermore, the intrinsic viscosity of the polyhexamethylene adipamide in step 1 at 25° C. is 0.27±0.02 dL / g.
[0024] Furthermore, the intrinsic viscosity of the polyphenylene ether in step 1 at 25° C. is 0.35±0.02 dL / g.
[0025] Furthermore, the compatibilizer in step 1 is maleic anhydride grafted polyphenylene ether.
[0026] Furthermore, the dispersant in step 1 is a compound of silicone powder and polyethylene wax in a mass ratio of (3-5): (1-3).
[0027] Furthermore, the reinforcing filler in step 2 is silicone-modified glass fiber.
[0028] Furthermore, the glass fibers in the organosilicon-modified glass fibers are flat chopped glass fibers, and the aspect ratio of the flat chopped glass fibers is 1:(3-3.75).
[0029] Furthermore, in the step 2, the mass ratio of the reinforcing filler to the polyhexamethylene adipamide is (25-35): (25-50).
[0030] Furthermore, in step 3, the mass ratio of the flame retardant, the flame retardant synergist and the polyhexamethylene adipamide is (10-16): (0.1-6): (25-50).
[0031] Furthermore, in step 3, the mixing speed is 300-500 r / min, and the mixing time is 2-4 min.
[0032] Furthermore, the flame retardant in step 3 is prepared by compounding diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of (3-4): 1:0.5.
[0033] Furthermore, the flame retardant synergist in step 3 is 2,3-dimethyl-2,3-diphenylbutane.
[0034] Furthermore, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 260-280°C, the temperature of the second temperature zone is 250-270°C, the temperature of the third temperature zone is 240-260°C, the temperature of the fourth temperature zone is 240-260°C, the temperature of the fifth temperature zone is 240-260°C, the temperature of the sixth temperature zone is 240-250°C, the temperature of the seventh temperature zone is 240-250°C, the temperature of the eighth temperature zone is 250-260°C and the temperature of the ninth temperature zone is 260-270°C.
[0035] Furthermore, the temperature at the main feeding hopper of the twin-screw extruder is 180-160°C.
[0036] Furthermore, the head temperature of the twin-screw extruder is 260-280°C.
[0037] A battery upper cover is prepared from the ablation-resistant composite material.
[0038] Beneficial effects of the present invention: 1. Conventional round glass fibers are used to enhance the mechanical properties of the alloy material of traditional polyphenylene ether and PA66 during the preparation process. However, in the present invention, flat glass fibers with a fixed aspect ratio are mixed with polyphenylene ether, etc., wherein the special flat shape makes the contact area with the matrix larger, and the stress can be better transmitted in the composite material, and the enhancement effect is more significant, especially in improving the bending modulus of the material. In addition, due to its flat shape, it is easier to overlap and orient each other during the mixing and molding process. Therefore, in the present invention, the silicone-modified flat glass fibers not only improve the mechanical properties of the material, but also rely on the overall formula and processing technology of the present invention to improve the surface smoothness of the material, so that the material does not produce floating fibers; 2. In addition to the special glass fiber material, the flame retardant in the present invention is diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder added in a fixed ratio. When diethyl aluminum hypophosphite and melamine hypophosphite are compounded, phosphorus-phosphorus or phosphorus-nitrogen synergistic effects can be exerted to form a denser and more stable carbonized layer on the surface of the material, effectively blocking heat and oxygen and inhibiting the spread of flames. After adding ceramic powder, the ceramic powder will form a solid ceramic layer at high temperature, further enhancing the barrier effect and significantly improving the flame retardant performance. Diethyl aluminum hypophosphite and melamine hypophosphite have little effect on the mechanical properties of the material itself and have high thermal stability. While being flame retardant, they can ensure the mechanical properties and temperature resistance of the material, so that the material will not collapse or burn through. It is halogen-free flame retardant and has good environmental protection. 3. In the present invention, a flame retardant is added to the flame retardant, wherein the flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane, which can seal the free radicals generated by the combustion of the material when the material is burned, thereby forming a cross-linking grafting effect, promoting the carbonization of the material, forming a stable carbon layer, effectively blocking the transfer of heat and oxygen, and preventing the further spread of the flame, thereby improving the flame retardant efficiency of the material, and having little effect on the physical and mechanical properties such as tensile strength of the polymer system, and being able to take into account both tensile properties and flame retardant properties, so that the material has good flame retardant effect and still maintains good mechanical properties. At the same time, it has good thermal stability and strong chemical stability, and when used as a battery cover, it has a longer service life; 4. In the present invention, fixed proportions of polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are first mixed in a twin-screw extruder to improve the dispersibility of the main components polyhexamethylene adipamide and polyphenylene ether. Then, a reinforcing filler is added in the fifth temperature zone of the twin-screw extruder to prevent the reinforcing filler from being excessively sheared and to maintain its original shape. Finally, a flame retardant and a flame retardant synergist are added to prevent thermal decomposition and other problems in the twin-screw extruder. The twin-screw extruder is subjected to a certain processing temperature. Under this specific proportion and processing conditions, the ablation-resistant composite material of the present invention that is resistant to ablation, has high mechanical properties and does not deform is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a surface state diagram of the ablation-resistant composite material in Example 1 after ablation resistance test; Figure 2 This is a surface state diagram of the ablation-resistant composite material in Comparative Examples 2 and 3 after ablation resistance testing; Figure 3 It is a surface state diagram of the ablation-resistant composite material in Example 4 and Comparative Example 1; Figure 4 This is a diagram of the deformation state of the ablation-resistant composite material described in Comparative Examples 5 and 6. DETAILED DESCRIPTION
[0040] The invention is described in detail below with reference to the embodiments: The invention provides an ablation-resistant composite material, which is prepared by mixing polyhexamethylene adipamide and polyphenylene ether and then adding a processing aid in a specific proportion to mix them, thereby greatly improving the ablation-resistant performance of the composite material.
[0041] Example 1 The present embodiment provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 43.3 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 126 MPa, a flexural strength of 166 MPa, and a simply supported beam notched impact strength of 5.3 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0042] In this embodiment, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 41 parts by weight; Polyphenylene ether is 15 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 13 parts by weight; The flame retardant synergist is 4 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0043] In this embodiment, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0044] This embodiment also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 300 r / min for 4 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0045] In this embodiment, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0046] like Figure 1 This is a diagram of the surface state of the ablation-resistant composite material in Example 1 after the ablation resistance test. In the diagram, the ablation-resistant composite material has no collapse and no burn-through after ablation at 1000° C. for 30 minutes.
[0047] Example 2 The present embodiment provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 54.6 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 138 MPa, a flexural strength of 172 MPa, and a simply supported beam notched impact strength of 6.4 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0048] In this embodiment, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 43 parts by weight; Polyphenylene ether is 15 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 10 parts by weight; The flame retardant synergist is 5 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0049] In this embodiment, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0050] This embodiment also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 500 r / min for 2 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 500 r / min for 2 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0051] In this embodiment, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0052] Example 3 The present embodiment provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 45.2 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 112 MPa, a flexural strength of 154 MPa, and a simply supported beam notched impact strength of 4.8 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0053] In this embodiment, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 37 parts by weight; Polyphenylene ether is 16 parts by weight; The reinforcing filler is 25 parts by weight; The flame retardant is 13 parts by weight; The flame retardant synergist is 4 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0054] In this embodiment, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0055] This embodiment also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 400 r / min for 3 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 400 r / min for 3 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0056] In this embodiment, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0057] Example 4 The present embodiment provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 46.8 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 132 MPa, a flexural strength of 168 MPa, and a simply supported beam notched impact strength of 5.6 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0058] In this embodiment, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 41 parts by weight; Polyphenylene ether is 10 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 15 parts by weight; The flame retardant synergist is 3 parts by weight; The compatibilizer is 3 parts by weight; The dispersant is 1 part by weight.
[0059] In this embodiment, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0060] This embodiment also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 300 r / min for 4 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0061] In this embodiment, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0062] Comparative Example 1 The comparative example provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist and dispersant; the ablation-resistant composite material has a melt index of 37.4 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 106 MPa, a flexural strength of 142 MPa, and a simply supported beam notched impact strength of 4.6 kJ / m 2 , no deformation at 0-120°C, and slight floating fibers on the surface; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0063] In this comparative example, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 41 parts by weight; Polyphenylene ether is 15 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 13 parts by weight; The flame retardant synergist is 4 parts by weight; The dispersant is 1 part by weight.
[0064] In this comparative example, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0065] This comparative example also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 300 r / min for 4 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0066] In this comparative example, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0067] like Figure 3 This is a surface state diagram of the ablation-resistant composite material in Example 4 and Comparative Example 1. In the figure, no floating fibers are generated on the surface of the ablation-resistant composite material in Example 4, while slight floating fibers appear on the surface of Comparative Example 1.
[0068] Comparative Example 2 The comparative example provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 66.5 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 98 MPa, a flexural strength of 136 MPa, and a simply supported beam notched impact strength of 3.8 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is less than 4 minutes.
[0069] In this comparative example, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 43 parts by weight; Polyphenylene ether is 15 parts by weight; The reinforcing filler is 15 parts by weight; The flame retardant is 10 parts by weight; The flame retardant synergist is 5 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0070] In this comparative example, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0071] This comparative example also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 300 r / min for 4 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0072] In this comparative example, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0073] Comparative Example 3 The comparative example provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 69.8 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 66 MPa, a flexural strength of 83 MPa, and a simply supported beam notched impact strength of 2.6 kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is less than 1min.
[0074] In this comparative example, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 37 parts by weight; Polyphenylene ether is 16 parts by weight; The flame retardant is 13 parts by weight; The flame retardant synergist is 4 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0075] In this comparative example, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0076] This comparative example also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 500 r / min for 2 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, mixing the flame retardant and the flame retardant synergist at a speed of 500 r / min for 2 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0077] In this comparative example, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0078] like Figure 2 This is a diagram of the surface state of the ablation-resistant composite materials described in Comparative Examples 2 and 3 after ablation resistance testing. In the diagram, after the materials are ablated at 1000° C., the material in Comparative Example 2 is not burned through, but collapses, while the material in Comparative Example 3 is burned through.
[0079] Comparative Example 4 The comparative example provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 53.8 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 146 MPa, a flexural strength of 175 MPa, and a simply supported beam notched impact strength of 7.2 kJ / m 2, slight deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is less than 8 minutes.
[0080] In this comparative example, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 41 parts by weight; Polyphenylene ether is 10 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 15 parts by weight; The compatibilizer is 3 parts by weight; The dispersant is 1 part by weight.
[0081] In this comparative example, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0082] This comparative example also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, feeding the flame retardant from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0083] In this comparative example, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0084] Comparative Example 5 The comparative example provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 31.7 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 118 MPa, a flexural strength of 158 MPa, and a simply supported beam notched impact strength of 4.8 kJ / m 2 , deformation at 0-120°C, and obvious floating fibers on the surface; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
[0085] In this comparative example, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 41 parts by weight; Polyphenylene ether is 25 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 13 parts by weight; The flame retardant synergist is 4 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0086] In this comparative example, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is silicone modified glass fiber, the manufacturer of the silicone modified glass fiber is Taishan Glass Fiber, the brand is TFG436, the glass fiber in the silicone modified glass fiber is flat chopped glass fiber, and the aspect ratio of the flat chopped glass fiber is 1:3.75; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0087] This comparative example also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 300 r / min for 4 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0088] In this comparative example, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0089] Comparative Example 6 The comparative example provides an ablation-resistant composite material, which is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 38.6 g / 10 min at 280° C. and a load of 5 kg, a tensile strength of 115 MPa, a flexural strength of 152 MPa, and a simply supported beam notched impact strength of 4.2 kJ / m 2 , deformation at 0-120°C, and obvious floating fibers on the surface; the burn-through time of the ablation-resistant composite material at 1000°C is less than 15min.
[0090] In this comparative example, the components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 41 parts by weight; Polyphenylene ether is 15 parts by weight; The reinforcing filler is 30 parts by weight; The flame retardant is 13 parts by weight; The flame retardant synergist is 4 parts by weight; The compatibilizer is 5 parts by weight; The dispersant is 1 part by weight.
[0091] In this comparative example, the intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g; The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g; The reinforcing filler is organosilicon-modified glass fiber, the organosilicon-modified glass fiber manufacturer is Taishan Glass Fiber, the brand is T436, and the glass fiber in the organosilicon-modified glass fiber is conventional cylindrical chopped glass fiber; The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of 3:1:0.5. The flame retardant synergist is sepiolite; The compatibilizer is maleic anhydride grafted polyphenylene ether; The dispersant is prepared by compounding silicone powder and polyethylene wax in a mass ratio of 3:2.
[0092] This comparative example also provides a method for preparing the ablation-resistant composite material, comprising the following steps: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed at a speed of 300 r / min for 4 minutes, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist at a speed of 300 r / min for 4 minutes, and feeding the mixture from the side feeding port of the seventh temperature zone of the twin-screw extruder through a loss-in-weight scale; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
[0093] In this comparative example, the processing temperature of the twin-screw extruder is 240-280°C, which is divided into nine temperature zones, wherein the temperature of the first temperature zone is 270°C, the temperature of the second temperature zone is 265°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 250°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the temperature of the seventh temperature zone is 240°C, the temperature of the eighth temperature zone is 250°C and the temperature of the ninth temperature zone is 260°C; the temperature at the main feeding hopper of the twin-screw extruder is 170°C; the head temperature of the twin-screw extruder is 265°C.
[0094] like Figure 4 3 is a deformation state diagram of the ablation-resistant composite material in Comparative Examples 5 and 6. It can be seen from the figure that the materials in Comparative Examples 5 and 6 are severely deformed.
[0095] Table 1 shows the components and contents of the ablation-resistant composite materials described in Examples 1-4 and Comparative Examples 1-6.
[0096] Table 2 shows the properties of the ablation-resistant composite materials described in Examples 1-4 and Comparative Examples 1-6
[0097] As shown in Tables 1 and 2, the materials in Examples 1-4 have good processability, good mechanical properties, no deformation at high temperature, no floating fibers, and are resistant to ablation, while in Comparative Example 1, no compatibilizer is added, and the compatibility between polyphenylene ether and polyhexamethylene adipamide and the reinforcing filler is poor, resulting in floating fibers on the surface of the material; in Comparative Example 2, less reinforcing filler is added, so the mechanical properties of the material are poor; in Comparative Example 3, no reinforcing filler is added, the mechanical properties are greatly reduced, the ablation resistance is less than 1 min, and there is almost no ablation resistance; In Comparative Example 4, no flame retardant synergist was added. Although the mechanical properties were improved, the ablation resistance was poor and slight deformation would occur. In Comparative Example 5, the content of polyphenylene ether was increased. However, polyphenylene ether has a high viscosity and poor compatibility when mixed with reinforcing fillers, resulting in severe floating fibers and deformation. In Comparative Example 6, the glass fiber was replaced with ordinary cylindrical glass fiber, and the flame retardant synergist was replaced with sepiolite from 2.3-dimethyl-2.3-diphenylbutane. The ablation resistance of the material deteriorated and the material would be severely deformed.
[0098] Based on the above, it can be seen that the ablation-resistant composite material of the present invention has a wide range of applications, low cost and extremely high market prospects.
[0099] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. An ablation-resistant composite material, characterized in that: The ablation-resistant composite material is prepared by melt mixing polyhexamethylene adipamide, polyphenylene ether, reinforcing filler, flame retardant, flame retardant synergist, compatibilizer and dispersant; the ablation-resistant composite material has a melt index of 40-55g / 10min at 280°C and a load of 5kg, a tensile strength of 110-140MPa, a flexural strength of 150-180MPa, and a simply supported beam notched impact strength of 4-7kJ / m 2 , no deformation at 0-120°C, smooth surface, and no floating fibers; the burn-through time of the ablation-resistant composite material at 1000°C is greater than 30 minutes.
2. The ablation-resistant composite material according to claim 1, characterized in that: The components and contents of the ablation-resistant composite material are as follows: Polyhexamethylene adipamide is 25-50 parts by weight; Polyphenylene ether is 10-30 parts by weight; The reinforcing filler is 25-35 parts by weight; The flame retardant is 10-16 parts by weight; The flame retardant synergist is 0.1-6 parts by weight; The compatibilizer is 0.1-6 parts by weight; The dispersant is 1-2 parts by weight.
3. The ablation-resistant composite material according to claim 1, characterized in that: The intrinsic viscosity of the polyhexamethylene adipamide at 25° C. is 0.27±0.02 dL / g.
4. The ablation-resistant composite material according to claim 1, characterized in that: The intrinsic viscosity of the polyphenylene ether at 25° C. is 0.35±0.02 dL / g.
5. The ablation-resistant composite material according to claim 1, characterized in that: The reinforcing filler is organic silicon modified glass fiber, the glass fiber in the organic silicon modified glass fiber is flat short glass fiber, and the aspect ratio of the flat short glass fiber is 1: (3-3.75).
6. The ablation-resistant composite material according to claim 1, characterized in that: The flame retardant is prepared by mixing diethyl aluminum hypophosphite, melamine hypophosphite and ceramic powder in a mass ratio of (3-4):1:0.
5.
7. The ablation-resistant composite material according to claim 1, characterized in that: The flame retardant synergist is 2,3-dimethyl-2,3-diphenylbutane.
8. The ablation-resistant composite material according to claim 1, characterized in that: The dispersant is prepared by mixing silicone powder and polyethylene wax in a mass ratio of (3-5): (1-3).
9. A method for preparing the ablation-resistant composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, polyhexamethylene adipamide, polyphenylene ether, a compatibilizer and a dispersant are mixed, and fed from a main feeding hopper of a twin-screw extruder through a loss-in-weight scale; Step 2, feeding the reinforcing filler from the side feeding port of the fifth temperature zone of the twin-screw extruder through a loss-in-weight scale; Step 3, mixing the flame retardant and the flame retardant synergist, and feeding the mixture through a loss-in-weight scale from a side feeding port in the seventh temperature zone of the twin-screw extruder; The polyhexamethylene adipamide, the polyphenylene ether, the reinforcing filler, the flame retardant, the flame retardant synergist, the compatibilizer and the dispersant are melt-mixed in the twin-screw extruder, extruded and pelletized to obtain the ablation-resistant composite material.
10. A battery cover, characterized in that: The battery top cover is made of the ablation-resistant composite material according to any one of claims 1-8.
Citation Information
Patent Citations
Ablation-resistant polyphenyl ether composition and preparation method thereof
CN115594970A